Advanced gastric cancer with lymph node metastasis successfully treated using multimodal therapy: a case report - Wei, Zhewei; Zheng, Jiabo; Hao, Tengfei; He, Yulong; Zhang, Changhua (Digestive Medicine Research; Vol 2 (January 2019): Digestive Medicine Research, 2019)
The emergence neo-adjuvant chemotherapy and multi-disciplinary team (MDT) approach has improved the prognosis of advanced gastric cancer in the recent years and our medical center has been implementing both treatment modality in the treatment of our surgical oncological patients. This case report describes a 64-year-old patient who was initially diagnosed with a cT4N2M0 gastric adenocarcinoma by CT, positron emission tomography (PET)-CT, gastroscopy with lesion biopsy and endoscopic ultrasound. After MDT discussion, the patient was treated with neo-adjuvant chemotherapy (5 SOX cycles), where marked remission was observed (under CT and gastroscopy), then she underwent surgical intervention with radical gastrectomy (D2 + PAND), followed by hyperthermic intraperitoneal chemotherapy (HIPEC) and adjuvant chemotherapy (6 SOX cycles). The patient was regularly followed up and underwent regular check-ups (CT and gastroscopy), and till last follow-up, the patient is alive and disease free. This shows that multi-modality treatment with peri-operative chemotherapy, appropriate surgical intervention and HIPEC may serve as a promising treatment combination for advanced gastric cancer.